PERAN KEPALA DESA DALAM PENYELESAIAN SENGKETA PEMBAGIAN TANAH WARISAN DI DESA MAKATAKERI KABUPATEN SUMBA TENGAH - Satrio Umbu Neka Pajaga (Kerta Dyatmika, 2022)
Conflict resolution in areas that still adhere to customary law involves local customary institutions, with traditional leaders providing advice and assistance to restore social relationships. Land dispute conflicts often arise in village communities due to population growth and social differences. The role of the village chief as a motivator, facilitator, and mediator is crucial in resolving conflicts comprehensively, with alternative dispute resolution through the village chief expected to be easier compared to going through the court system. The research used empirical methods with literature studies. Data were collected from primary and secondary sources through document studies, observations, and interviews. Data analysis was conducted qualitatively descriptively to provide a clear basis. The study aims to examine the role of the village chief in resolving inheritance land disputes in Makatakeri Village, Central Sumba Regency, and to study the dispute resolution system. Based on the research results, the role of the Makatakeri village chief as a mediator has been maximized for the benefit of the community, and the Makatakeri Village community prefers dispute resolution through the village chief rather than through the courts because it is considered cheaper and more satisfactory. The procedure for resolving inheritance disputes through mediation in Makatakeri Village is as follows: pre-mediation stage, mediation process stage, reaching agreement through mediation, and post-mediation stage.